Decoding YOD1: Insights into tumour regulation and translational opportunities - Zhi-Xiong, Chong (Biochemical pharmacology, 2025)
[Display omitted] YOD1 deubiquitinase is a 38 kDa protein that belongs to the ovarian tumour protease (OTU) family, and its dysregulation can precipitate cancer development. Still, an up-to-date review article that can summarize its detailed tumour-regulatory function and translational potentials in different cancer types is lacking. To fill this literature gap, this review aims to discuss the tumour-modulatory role of YOD1 based on findings from different pre-clinical and clinical studies, followed by exploring the potential translational values of YOD1 as a tumour biomarker or therapeutic target. Overall, YOD1 could control the development of at least 15 tumour types by deubiquitinating or targeting different cellular proteins to modulate the activities of the cell cycle, p53, β-catenin, extracellular-regulated signal kinase (ERK), and YES-associated pathway (YAP) activities. Additionally, four long non-coding RNAs (lncRNAs), 12 microRNAs (miRNAs), and a few compounds can also directly or indirectly alter the expression and activity of YOD1, mediating tumourigenesis across different cancer types. Cellular expression data showed that YOD1 expression is dysregulated in eight cancer types, giving YOD1 the potential to be used as a diagnostic biomarker. Besides, YOD1 dysregulation can affect the clinical outcomes of various cancers. Hence, targeting YOD1 could potentially help slow tumourigenesis. The major drawback of considering YOD1 as a biomarker or therapeutic target is that its tumour-regulatory role is mainly based on the findings from single-center studies with relatively small sample sizes. Hence, future large-scale and in-depth clinical trials should be conducted to further verify the translational values of YOD1 as a biomarker or therapeutic target.